(untitled) (Baghdad Science Journal, 2019)
The telecommunications industry has gone through series of development efforts to provide quality services to their consumers. Generally, telecommunication industry provides two main services such as telephony and internet which involved customer registration, billing and payment. However, the challenge confronting telecommunications industry is to meet the customer satisfaction in the billing system such as accuracy, easy to understand and unambiguous billing issue. In order to develop Customer Billing Telephony System,a user experience study is conducted to gather the user requirements. Hence, the CBTS was developed that takes into consideration user’s value experience that provides a support for managing and monitoring billing process. Then the CBTS was evaluated by the users using User Experience Questionnaire (UEQ) to prove the efficiency and correctness in billing process. The result shown that the users give the positive feedback of the CBTS.